UPAYA PENINGKATAN HASIL BELAJAR SISWA PADA KONSEP RANGKAIAN LISTRIK ARUS SEARAH DENGAN MENGGUNAKAN KIT FISIKA - Idawati Idawati (JURNAL FISIKA EDUKASI, 2015)
The purpose of this study was to determine: a) the activities of teachers and students; b) the ability of teachers to manage teaching and learning; c) the response of teachers and students to use KIT KBM physics and (d) an increase in student achievement by using KIT physics concept of direct current electrical circuit. The subjects in this reasearch is class XII-IA-1 SMA Negeri 4 Banda Aceh with the number of students 32 student. Data analysis using descriptive analysis is the percentage (%). Based on the results of data analysis can be concluded: (a) Activities of teachers is the most dominant discuss experimental results (15.55%), guiding students conduct experiments (15.18%), guiding students summed up the results of experiments (11.48%). While the most prominent activity is conducted experiments (25.40%), ask questions/express ideas (13.83%), and express opinions / ideas (13.66%). This is in accordance with the steps in the use of KIT physics; (b) The ability of teachers to manage learning using physics KIT categorized quite good; (c) The response of students to use the device and learning physics KIT is 89.6% of students interested in participating in further learning activities and (d) use the KIT physics learning can improve student achievement on the concept of direct current electrical circuit by 82%. This shows that in general the students have to know and understand the concept of direct current electrical circuits by using KIT teaching physics.